Discrimination of cytosolic self and non-self RNA by RIG-I-like receptors - Lässig, Charlotte (J Biol Chem, 2017)
RIG-I-like receptors (RLRs) are cytosolic innate immune sensors that detect pathogenic RNA and induce a systemic antiviral response. During the last decade, many studies focused on their molecular characterization and the identification of RNA agonists. Therefore, it became more and more clear that RLR activation needs to be carefully regulated, because constitutive signaling or detection of endogenous RNA through loss of specificity is detrimental. Here, we review the current understanding of RLR activation and selectivity. We specifically focus upon recent findings on the function of the helicase domain in discriminating between different RNAs, and whose malfunctioning causes serious autoimmune diseases.